Functional Classification of the ATM Variant c.7157C>A and In Vitro Effects of Dexamethasone - Biagiotti, Sara; Barone, Ambra; Aliano, Mattia Paolo; Federici, Giulia; Malatesta, Marco; Caputi, Caterina; Soddu, Silvia; Leuzzi, Vincenzo; Chessa, Luciana; Magnani, Mauro (Frontiers in Genetics, 2021)
Most of the ATM variants associated with Ataxia Telangiectasia are still classified as variants with uncertain significance. Ataxia Telangiectasia is a multisystemic disorder characterized by “typical” and “atypical” phenotypes, with early-onset and severe symptoms or with late-onset and mild symptoms, respectively. Here we classified the c.7157C>A ATM variant found in homozygosity in two brothers of Lebanese ethnicity. The brothers presented with an atypical phenotype, showing less than 50% of the positive criteria considered for classification. We performed several in silico analyses to predict the effect of c.7157C>A at the DNA, mRNA and protein levels, revealing that the alteration causes a missense substitution in a highly conserved alpha helix in the FAT domain. 3D structural analyses suggested that the variant might be pathogenic due to either loss of activity or to a structural damage affecting protein stability. Our subsequent in vitro studies showed that the second hypothesis is the most likely, as indicated by the reduced protein abundance found in the cells carrying the variant. Moreover, two different functional assays showed that the mutant protein partially retains its kinase activity. Finally, we investigated the in vitro effect of Dexamethasone showing that the drug is able to increase both protein abundance and activity. In conclusion, our results suggest that the c.7157C>A variant is pathogenic, although it causes an atypical phenotype, and that dexamethasone could be therapeutically effective on this and possibly other missense ATM variants.